CIVIL FLIGHT GUIDE WHEN TAKE OFF FROM THE GADING FIELD - Maria Ermelinda Bupu (Institut Teknologi Dirgantara Adisutjipto, 2021)
Until now, Gading Airfield cannot be used for commercial flights. However, in the future, along with the increasing number of commercial and training flights, Gading Airfield will continue to be developed to help smooth flights in DI Yogyakarta. Thus some flight guidelines for civil aviation must be made. Several analysis and calculation methods are carried out starting from general analysis of the airfield, counting and design of the takeoff guide patron starting from two sides of the runway, namely from RWY 10 and 28. The calculation consists of MTOW calculation which is limited by PCN, calculation of takeoff path, calculation Takeoff distance requirement, calculation of climb segment up to 1.500 feet, calculation of flight turn 1.500 feet, to design patron takeoff path guidance.